P Pendampingan Perizinan Bangunan Gedung (PBG) untuk bangunan Gudang di Komplek Pergudangan Kabupaten Banjar - Alkausar, Alkausar; Hafizha, Farah; Yuniar, Annisa; Hidayat, Muya Ryan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
Building Licences or abbreviated as PBG is a permit given from the local government to the owner of the building to build a new building, change, expand, reduce, and maintain the building in accordance with the technical standards of the building. This activity aims to assist building/warehouse owners to obtain building permits that have not completed the technical drawing document requirements. This activity took place for 6 days on Monday 18-23 December 2023. The method used is by surveying the warehouse to be able to make raw data such as surveying building plans, pole sizes and other things that are considered important to complete the drawing requirements. Then make the requirements for the completeness of the required documents in the form of architectural and structural technical drawings. Based on the results of the PBG assistance, the drawings produced are in accordance with the request of the Banjar district government regulations, namely 8 sheets of architectural technical drawings and 10 sheets of structural technical drawings. This activity is expected to make it important to complete the document requirements in the form of drawings and others before starting the construction process.